Bilateral metastatic breast cancer as the first manifestation of ovarian cancer: case report - (:unkn) unknown (My University, 2005)
BACKGROUND: Breast metastasis from primary ovarian cancer is extremely rare. The rarity of this finding may be the reason for its common misinterpretation as primary breast carcinoma. DESIGN: Case report. SETTING: A university hospital. RESULTS: A case of a patient with primary ovarian papillary serous cystadenocarcinoma who initially presented with a solitary bilateral breast mass and abdominal distention is reported. CONCLUSIONS: Blood-borne metastasis from the ovary to the breast can show a varied clinical picture that should be differentiated from that of primary breast carcinoma.
Keywords: Female; Humans; Aged; Ovarian Neoplasms; Antineoplastic Combined Chemotherapy Protocols; Breast Neoplasms; Cystadenocarcinoma; Carboplatin; Gynecologic Surgical Procedures; Paclitaxel